"When Appearances Matter: A Taxonomy and Ethics for Demographic-Based Provider Requests" - Wu, Carrie C. (Cambridge quarterly of healthcare ethics, 2023)
Requests by patients for providers of specific demographic backgrounds pose an ongoing challenge for hospitals, policymakers, and ethicists. These requests may stem from a wide variety of motivations; some may be consistent with broader societal values, although many others may reflect prejudices inconsistent with justice, equity, and decency. This paper proposes a taxonomy designed to assist healthcare institutions in addressing such cases in a consistent and equitable manner. The paper then reviews a range of ethical and logistical challenges raised by such requests and proposed guidance to consider when reviewing and responding to them.